Injectable self-adhesive gel as well as preparation method and application thereof

By developing an injectable self-adhesive gel, using the combination of polyelectrolyte composite particles and oil-phase dispersant, the problems of existing aneurysm embolization materials such as poor sealing, coagulation disorders, high mechanical strength and solvent toxicity have been solved, and the problem of existing aneurysm embolization materials has been achieved. The effects of rapid gelation, strong adhesion and excellent biocompatibility.

CN119455064APending Publication Date: 2025-02-18ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411623993.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing aneurysm embolization materials have problems such as poor sealing, unsuitable for patients with coagulation disorders, high mechanical strength leads to changes in blood vessel shape and inflammatory response, and solvent biotoxicity.

Method used

A bioadhesive gel is developed to prepare a bioadhesive agent by mixing oil-phase dispersant and polyelectrolyte composite particles. Polyelectrolyte composite particles achieve long-term and stable adhesion of the tissue surface through covalent bonding of phenylboric acid.

Benefits of technology

Rapid gelation, strong tissue adhesion and excellent biocompatibility are achieved, reducing the compression and toxicity risks of vascular walls by the long-term implantation of embolizing materials in the blood vessels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455064A_ABST
    Figure CN119455064A_ABST
Patent Text Reader

Abstract

The invention discloses injectable self-adhesive gel, a preparation method thereof and application of the injectable self-adhesive gel in preparation of a vascular embolism material. The injectable self-adhesive gel comprises an oil phase dispersing agent and polyelectrolyte compound particles uniformly dispersed in the oil phase dispersing agent; the polyelectrolyte compound particles are obtained by coagulation, drying and ball milling of phenylboronic acid modified cationic polyelectrolyte and anionic polyelectrolyte in a solution. The preparation method comprises the following steps: introducing a phenylboronic acid group in a manner of covalent grafting of a molecule with the phenylboronic acid group and a cationic polyelectrolyte to obtain the phenylboronic acid modified cationic polyelectrolyte; carrying out coagulation, drying and ball milling on the phenylboronic acid modified cationic polyelectrolyte and anionic polyelectrolyte in a solution to obtain polyelectrolyte compound particles; and uniformly dispersing the polyelectrolyte compound particles in an oil phase dispersant to obtain the injectable self-adhesive gel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of vascular embolic materials, and in particular to an injectable self-adhesive gel and a preparation method and application thereof. Background Art

[0002] Aneurysm disease is a typical vascular malformation, which is mainly caused by the expansion or bulging of the diseased arterial wall under the impact of blood flow. Once the aneurysm ruptures, it will lead to uncontrolled bleeding, with a mortality rate of more than 40%, which seriously threatens human life and health.

[0003] The commonly used clinical treatment for aneurysm disease is to inject a mechanical embolic metal coil into the lesion through a catheter to fill the aneurysm body, and further induce thrombosis to block the blood vessels and blood supply, thereby reducing the possibility of aneurysm rupture.

[0004] However, metal spring coils have poor sealing properties during application, and there is a chance of incomplete embolism. Moreover, part of the cause of embolism depends on thrombosis, and it is not suitable for patients with coagulation disorders. In addition, spring coils are mostly made of platinum materials, and their mechanical strength is much higher than that of vascular tissue. After implantation, this type of high-strength, rigid metal device will change the original geometry of the blood vessels, affect vascular hemodynamics, induce inflammatory response, and destroy endothelial function. Its long-term implantation in blood vessels is prone to further complications such as foreign body reaction and coil displacement.

[0005] Therefore, people hope to develop more flexible, mechanically adaptable, and biocompatible embolic materials for aneurysm embolization.

[0006] In contrast, liquid embolic agents provide an alternative treatment to metal coils. Their advantage is that they can be shaped according to the morphology of the aneurysm cavity during injection, reducing the generation of dead space. In addition, this filling form does not rely on thrombosis and has better blood compatibility than metal implants.

[0007] The most representative liquid embolic agent is the commercial product Onyx, which has been approved by the FDA for embolization of intracranial arteriovenous malformations. However, it is expensive and requires high surgical operation. In addition, the solvent dimethyl sulfoxide (DMSO) it contains has certain biological toxicity and is prone to cause vascular toxicity and necrosis.

[0008] The rise of the field of injectable hydrogels in recent years has also provided more solutions for aneurysm embolization. Injectable hydrogels are considered to be a more biocompatible solution. Current studies have reported that injectable hydrogels based on alginate, gelatin, etc. show embolic effects similar to those of metal coils. However, many hydrogels easily swell in the blood environment, exerting unnecessary pressure on the blood vessel wall. In addition, most of the current injectable embolic materials do not have tissue adhesion, and their interaction with vascular tissue is weak or even nonexistent. Under high physiological pressure, the gel is prone to fall off and shift, affecting the effect of embolic treatment.

[0009] In summary, it is necessary to develop new flexible embolic materials and embolic strategies that have mechanical adaptability, high filling rate, low swelling rate, strong tissue adhesion and excellent biocompatibility. Summary of the invention

[0010] In view of the above technical problems and the deficiencies in the art, the present invention provides an injectable self-adhesive gel and a preparation method and application thereof.

[0011] [1] An injectable self-adhesive gel comprising an oil phase dispersant and polyelectrolyte complex particles uniformly dispersed in the oil phase dispersant;

[0012] The polyelectrolyte complex particles are obtained by coagulating, drying and ball milling a cationic polyelectrolyte and an anionic polyelectrolyte modified with phenylboronic acid in a solution (specifically, an aqueous solution, etc.).

[0013] The present invention provides an injectable self-adhesive gel, which is prepared by mixing an oil phase dispersant and polyelectrolyte complex particles, so that the injectable bioadhesive can flow into the cavity and take shape after being injected into a blood vessel. Through solvent exchange with water or blood, the chain mobility of the polyelectrolyte complex particles is enhanced, and inter-particle fusion occurs to achieve rapid gelation. At the same time, the polyelectrolyte chain movement is used to diffuse into the tissue to achieve physical entanglement, and further through the covalent bonding of phenylboronic acid, long-term stable adhesion is achieved on the tissue surface, which is expected to achieve blood vessel blocking and embolism.

[0014] The modified cationic polyelectrolyte of phenylboronic acid can be obtained by covalently grafting a molecule with a phenylboronic acid group with a cationic polyelectrolyte. Further, the molecule with a phenylboronic acid group may include at least one of 3-acrylamide phenylboronic acid, 4-carboxyl phenylboronic acid, and 3,4-dicarboxyl phenylboronic acid. The covalent grafting may include at least one of a Michael addition reaction and an amidation reaction, and these reaction operations themselves are conventional technical means for those skilled in the art. In a preferred embodiment, 3-acrylamide phenylboronic acid is synthesized by a Michael addition reaction of an amino group to form a cationic polyelectrolyte with a phenylboronic acid group covalently grafted thereon (i.e., the modified cationic polyelectrolyte of phenylboronic acid), which has a higher reaction efficiency.

[0015] In some embodiments, the grafting rate of phenylboronic acid groups in the modified phenylboronic acid cationic polyelectrolyte is 1% to 20%, preferably 2% to 10%. In the present invention, the grafting rate of phenylboronic acid groups refers to the molar ratio of phenylboronic acid groups to repeating units in the cationic polyelectrolyte.

[0016] The cationic polyelectrolyte in the cationic polyelectrolyte modified with phenylboronic acid may include at least one of polyethyleneimine (PEI), polylysine (PLL), poly(lysine-leucine) (PKL), chitosan (CS), etc., which are polyelectrolytes widely studied for biomedical applications and have excellent biocompatibility.

[0017] The anionic polyelectrolyte may include at least one of polyacrylic acid (PAA), hyaluronic acid (HA), heparin, etc., all of which have excellent biocompatibility.

[0018] The mass ratio of the oil phase dispersant to the polyelectrolyte complex particles may be 4 to 12:1, preferably 6 to 9:1.

[0019] The weight average molecular weights of the cationic polyelectrolyte and the anionic polyelectrolyte in the cationic polyelectrolyte modified with phenylboronic acid can be independently 10,000 to 400,000 g / mol. Considering the solubility and chain mobility of the polyelectrolyte and the stability of the polyelectrolyte complex, they are preferably independently 10,000 to 200,000 g / mol, for example, 40000 g / mol, 50000 g / mol, 70000 g / mol, 100000 g / mol, etc.

[0020] The polyelectrolyte complex particles can be obtained by coagulating, drying and ball milling a cationic polyelectrolyte modified with phenylboronic acid and an anionic polyelectrolyte in a solution at a molar ratio of 0.1 to 5:1.

[0021] The particle size of the polyelectrolyte complex particles can be 1 to 100 microns, preferably 5 to 10 microns. The particle size of the polyelectrolyte complex particles can be controlled by ball milling conditions (rotation speed, time, etc.), and experiments have shown that particles of 5 to 10 μm can achieve rapid and reliable gelation.

[0022] In some embodiments, the particle size of the polyelectrolyte complex particles is no greater than or less than 10 microns.

[0023] The oil phase dispersant may include at least one of glycerol, linoleic acid, etc., all of which have excellent biocompatibility.

[0024] In some embodiments, the oil phase dispersant includes glycerol and linoleic acid. Further, in the oil phase dispersant, the volume ratio of glycerol to linoleic acid may be 0.2 to 5:1.

[0025] [2] The method for preparing the injectable self-adhesive gel according to [1], comprising:

[0026] Phenylboronic acid groups are introduced by covalently grafting molecules with phenylboronic acid groups with cationic polyelectrolytes to obtain cationic polyelectrolytes modified with phenylboronic acid;

[0027] The cationic polyelectrolyte and the anionic polyelectrolyte modified with phenylboronic acid are coagulated, dried, and ball-milled in a solution (specifically, an aqueous solution, etc.) to obtain polyelectrolyte complex particles;

[0028] The polyelectrolyte complex particles are uniformly dispersed in an oil phase dispersant to obtain the injectable self-adhesive gel.

[0029] [3] Use of the injectable self-adhesive gel according to [1] in the preparation of vascular embolic materials.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The injectable self-adhesive gel of the present invention can be prepared by mixing an oil phase dispersant and polyelectrolyte complex particles, which is a new application mode for polyelectrolyte complexes. The chain movement and entanglement of polyelectrolytes enable them to form a network structure more quickly and fully after encountering water, and penetrate into the tissue to achieve more stable tissue adhesion.

[0032] (2) By introducing phenylboronic acid groups, the gel can be quickly adhered to the tissue surface, so that it can be fixed at the lesion and is not prone to falling off or displacement. The phenylboronic acid group can quickly combine with 1,2- or 1,3-cis-diol to form a cyclic ester through covalent interaction, thereby firmly adhering to the tissue surface. This type of adhesion strategy is generally applicable to various tissues with mucus layers on the surface, such as the airway, esophagus, and lungs in the body.

[0033] (3) The injectable self-adhesive gel of the present invention uses glycerol or the like as the oil phase dispersant, which has better biosafety than the solvent DMSO used in the commercial Onyx product.

[0034] (4) Different from the irregular volume swelling of hydrogels in a wet environment, the swelling rate and stability of the polyelectrolyte of the present invention are more suitable for long-term implantation in the body without causing compression to the blood vessel wall. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a scanning electron microscope photo of the polyelectrolyte complex particles of Example 1, where the scale bar represents 10 microns;

[0036] Figure 2 This is the change of gel adhesion strength after modification with phenylboronic acid;

[0037] Figure 3 This is a comparison chart of the embolic pressure of the self-adhesive gel of Example 1 (PEA-B) and the gel of Comparative Example 1 (CA). DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0039] Unless otherwise specified, the weight average molecular weight (Mw) in the following examples is expressed in g / mol.

[0040] Example 1

[0041] Preparation and application of PEI-PBA / PAA injectable self-adhesive gel

[0042] (1) Synthesis of phenylboronic acid modified polyethyleneimine

[0043] 3-Acrylamidophenylboronic acid and polyethyleneimine (PEI, Mw = 70000, 50% aqueous solution) were added to a round-bottom flask at a mass ratio of 1:25, and a mixed solution of water and DMSO (volume ratio 1:1) was added and stirred thoroughly. The flask was placed in an oil bath at 60°C for 24 hours, and the yellow transparent solution was dialyzed in water for 3-4 days. The dialyzed solution was freeze-dried to obtain phenylboronic acid-modified polyethyleneimine (PEI-PBA).

[0044] (2) Preparation of polyelectrolyte complex particles

[0045] The polyethyleneimine modified with phenylboronic acid (PEI-PBA) and polyacrylic acid (PAA, Mw = 100000) were dissolved in water to prepare a 10wt% aqueous solution. The two solutions were mixed at a volume ratio of 0.5:1 under rapid stirring, and the polyelectrolyte complex was obtained by rapid coagulation. After freeze drying for 48 hours, the polyelectrolyte complex particles were obtained by grinding in a ball mill (4000rpm, 10min). The scanning electron microscope image of the particles is shown in FIG. Figure 1 As shown, the particle size is less than 10 μm.

[0046] (3) Preparation and application of injectable self-adhesive gel

[0047] The polyelectrolyte complex particles obtained in (2) were mixed with glycerol in a mass ratio of 1:6 and stirred thoroughly to make them uniformly dispersed, thereby obtaining an injectable self-adhesive gel (PEA-B). The gel could be smoothly extruded through a needle and a catheter, filling and adhering to the vascular wall of the rat abdominal aorta. Figure 2 As shown, the peeling test results show that the adhesion strength of the self-adhesive gel (PEA-B) on the surface of the bovine heart tube is significantly improved compared with the PEI / PAA composite gel (PEA) without modified phenylboronic acid groups, while the comparative example 1 gel (CA) has no adhesion.

[0048] The preparation process of PEI / PAA composite gel (PEA) is similar to that of PEA-B self-adhesive gel, that is, polyethyleneimine (PEI, Mw = 70000, 10wt% aqueous solution) and polyacrylic acid (PAA, Mw = 100000, 10wt% aqueous solution) are rapidly stirred and mixed at a volume ratio of 0.5:1, and coagulated to obtain a polyelectrolyte complex. After freeze drying and grinding (4000rpm, 10min), polyelectrolyte complex particles with a particle size of less than 10μm can be obtained, and then uniformly dispersed in glycerol to obtain PEI / PAA composite gel (the mass ratio of particles to glycerol is 1:6).

[0049] Example 2

[0050] Preparation and application of PEI-PBA / PAA injectable self-adhesive gel

[0051] (1) Synthesis of phenylboronic acid modified polyethyleneimine

[0052] 3-Acrylamidophenylboronic acid and polyethyleneimine (PEI, Mw = 70000, 50% aqueous solution) were added to a round-bottom flask at a mass ratio of 1:25, and a mixed solution of water and DMSO (volume ratio 1:1) was added and stirred thoroughly. The flask was placed in an oil bath at 60°C for 24 hours, and the yellow transparent solution was dialyzed in water for 3-4 days. The dialyzed solution was freeze-dried to obtain phenylboronic acid-modified polyethyleneimine (PEI-PBA).

[0053] (2) Preparation of polyelectrolyte complex particles

[0054] The polyethyleneimine modified with phenylboronic acid (PEI-PBA) and polyacrylic acid (PAA, Mw = 100000) were dissolved in water to prepare a 10wt% aqueous solution, and the two solutions were mixed at a volume ratio of 1:1 under rapid stirring, and the polyelectrolyte complex was obtained by rapid coagulation. After freeze drying for 48 hours, the polyelectrolyte complex particles with a particle size of less than 10μm were obtained by grinding in a ball mill (4000rpm, 10min).

[0055] (3) Preparation and application of injectable self-adhesive gel

[0056] The polyelectrolyte complex particles obtained in (2) were mixed with glycerol in a mass ratio of 1:6, and stirred thoroughly to make them uniformly dispersed, thereby obtaining an injectable self-adhesive gel. The gel can be smoothly extruded through a needle and a catheter, and fills and adheres to the vascular wall of the abdominal aorta of a rat.

[0057] Example 3

[0058] Preparation and application of PEI-PBA / PAA injectable self-adhesive gel

[0059] (1) Synthesis of phenylboronic acid modified polyethyleneimine

[0060] 3-Acrylamidophenylboronic acid and polyethyleneimine (PEI, Mw = 40000) were added to a round-bottom flask at a mass ratio of 1:10, and a mixed solution of water and DMSO (volume ratio 1:1) was added and stirred thoroughly. The flask was placed in an oil bath at 60°C for 24 hours, and the yellow transparent solution was dialyzed in water for 3-4 days. The dialyzed solution was freeze-dried to obtain phenylboronic acid-modified polyethyleneimine (PEI-PBA).

[0061] (2) Preparation of polyelectrolyte complex particles

[0062] The polyethyleneimine modified with phenylboronic acid (PEI-PBA) and polyacrylic acid (PAA, Mw = 70000) were dissolved in water to prepare a 10wt% aqueous solution, and the two solutions were mixed at a volume ratio of 0.75:1 under rapid stirring, and the polyelectrolyte complex was obtained by rapid coagulation. After freeze drying for 48 hours, the polyelectrolyte complex particles with a particle size of less than 10μm were obtained by grinding in a ball mill (4000rpm, 10min).

[0063] (3) Preparation and application of injectable self-adhesive gel

[0064] The polyelectrolyte complex particles obtained in (2) were mixed with glycerol in a mass ratio of 1:6, and stirred thoroughly to make them uniformly dispersed, thereby obtaining an injectable self-adhesive gel. The gel can be smoothly extruded through a needle and a catheter, and fills and adheres to the vascular wall of the abdominal aorta of a rat.

[0065] Example 4

[0066] Preparation and application of PEI-PBA / PAA injectable self-adhesive gel

[0067] (1) Synthesis of phenylboronic acid modified polyethyleneimine

[0068] 3-Acrylamidophenylboronic acid and polyethyleneimine (PEI, Mw = 40000) were added to a round-bottom flask at a mass ratio of 1:25, and a mixed solution of water and DMSO (volume ratio 1:1) was added and stirred thoroughly. The flask was placed in an oil bath at 60°C for 24 hours, and the yellow transparent solution was dialyzed in water for 3-4 days. The dialyzed solution was freeze-dried to obtain phenylboronic acid-modified polyethyleneimine (PEI-PBA).

[0069] (2) Preparation of polyelectrolyte complex particles

[0070] The polyethyleneimine modified with phenylboronic acid (PEI-PBA) and polyacrylic acid (PAA, Mw = 70000) were dissolved in water to prepare a 10wt% aqueous solution, and the two solutions were mixed at a volume ratio of 1.5:1 under rapid stirring, and the polyelectrolyte complex was obtained by rapid coagulation. After freeze drying for 48 hours, the polyelectrolyte complex particles with a particle size of less than 10μm were obtained by grinding in a ball mill (4000rpm, 10min).

[0071] (3) Preparation and application of injectable self-adhesive gel

[0072] The polyelectrolyte complex particles obtained in (2) were mixed with glycerol in a mass ratio of 1:6, and stirred thoroughly to make them uniformly dispersed, thereby obtaining an injectable self-adhesive gel. The gel can be smoothly extruded through a needle and a catheter, and fills and adheres to the vascular wall of the abdominal aorta of a rat.

[0073] Example 5

[0074] Preparation and application of PLL-PBA / HA injectable self-adhesive gel

[0075] (1) Synthesis of polylysine modified with phenylboronic acid

[0076] 3-Acrylamidophenylboronic acid and polylysine (PLL, Mw = 50000) were added to a round-bottom flask at a mass ratio of 1:10, and a mixed solution of water and DMSO (volume ratio 1:1) was added and stirred thoroughly. The flask was placed in an oil bath at 60°C for 24 hours, and the yellow transparent solution was dialyzed in water for 3-4 days. The dialyzed solution was freeze-dried to obtain polylysine modified with phenylboronic acid (PLL-PBA).

[0077] (2) Preparation of polyelectrolyte complex particles

[0078] Phenylboronic acid-modified polylysine (PLL-PBA) and hyaluronic acid (HA, Mw = 100000) were dissolved in water to prepare a 10wt% aqueous solution, and the two solutions were mixed at a volume ratio of 1:1 under rapid stirring, and the polyelectrolyte complex was obtained by rapid coagulation. After freeze drying for 48 hours, the polyelectrolyte complex particles with a particle size of less than 10μm were obtained by grinding in a ball mill (4000rpm, 10min).

[0079] (3) Preparation and application of injectable self-adhesive gel

[0080] The polyelectrolyte complex particles obtained in (2) were mixed with glycerol in a mass ratio of 1:7, and stirred thoroughly to make them uniformly dispersed, thereby obtaining an injectable self-adhesive gel. The gel can be smoothly extruded through a needle and a catheter, and fills and adheres to the vascular wall of the abdominal aorta of a rat.

[0081] Example 6

[0082] Preparation and application of PEI-PBA / HEP injectable self-adhesive gel

[0083] (1) Synthesis of phenylboronic acid modified polyethyleneimine

[0084] 3-Acrylamidophenylboronic acid and polyethyleneimine (PEI, Mw = 70000, 50% aqueous solution) were added to a round-bottom flask at a mass ratio of 1:20, and a mixed solution of water and DMSO (volume ratio 1:1) was added and stirred thoroughly. The flask was placed in an oil bath at 60°C for 24 hours, and the yellow transparent solution was dialyzed in water for 3-4 days. The dialyzed solution was freeze-dried to obtain phenylboronic acid-modified polyethyleneimine (PEI-PBA).

[0085] (2) Preparation of polyelectrolyte complex particles

[0086] The polyethyleneimine modified with phenylboronic acid (PEI-PBA) and heparin (HEP, Mw = 10000) were dissolved in water to prepare a 10wt% aqueous solution, and the two solutions were mixed at a volume ratio of 0.5:1 under rapid stirring, and the polyelectrolyte complex was obtained by rapid coagulation. After freeze drying for 48 hours, the polyelectrolyte complex particles with a particle size of less than 10μm were obtained by grinding in a ball mill (4000rpm, 10min).

[0087] (3) Preparation and application of injectable self-adhesive gel

[0088] The polyelectrolyte complex particles obtained in (2) were mixed with glycerol in a mass ratio of 1:8, and stirred thoroughly to make them uniformly dispersed, thereby obtaining an injectable self-adhesive gel. The gel can be smoothly extruded through a needle and a catheter, and fills and adheres to the vascular wall of the abdominal aorta of a rat.

[0089] Example 7

[0090] Preparation and application of PEI-PBA / PAA injectable self-adhesive gel

[0091] (1) Synthesis of phenylboronic acid modified polyethyleneimine

[0092] 3-Acrylamidophenylboronic acid and polyethyleneimine (PEI, Mw = 70000, 50% aqueous solution) were added to a round-bottom flask at a mass ratio of 1:25, and a mixed solution of water and DMSO (volume ratio 1:1) was added and stirred thoroughly. The flask was placed in an oil bath at 60°C for 24 hours, and the yellow transparent solution was dialyzed in water for 3-4 days. The dialyzed solution was freeze-dried to obtain phenylboronic acid-modified polyethyleneimine (PEI-PBA).

[0093] (2) Preparation of polyelectrolyte complex particles

[0094] The polyethyleneimine modified with phenylboronic acid (PEI-PBA) and polyacrylic acid (PAA, Mw = 100000) were dissolved in water to prepare a 10wt% aqueous solution, and the two solutions were mixed at a volume ratio of 1:1 under rapid stirring, and the polyelectrolyte complex was obtained by rapid coagulation. After freeze drying for 48 hours, the polyelectrolyte complex particles with a particle size of less than 10μm were obtained by grinding in a ball mill (4000rpm, 10min).

[0095] (3) Preparation and application of injectable self-adhesive gel

[0096] The polyelectrolyte complex particles obtained in (2) were mixed with linoleic acid in a mass ratio of 1:6, and stirred thoroughly to make them uniformly dispersed, thereby obtaining an injectable self-adhesive gel. The gel can be smoothly extruded through a needle and a catheter, and fills and adheres to the vascular wall of the abdominal aorta of a rat.

[0097] Comparative Example 1

[0098] Preparation and application of sodium alginate-calcium ion injectable gel

[0099] (1) Preparation of sodium alginate-calcium ion injectable gel

[0100] Sodium alginate and calcium chloride were dissolved in water respectively, and stirred sufficiently to prepare a 4 wt % aqueous solution.

[0101] (2) Application of sodium alginate-calcium ion injectable gel

[0102] The two solutions obtained in step (1) were co-injected at a mass ratio of 1:1. After mixing, a gel was quickly formed, which could be used for embolization of the lumen. The bursting pressure of the lumen after embolization was measured using a pressure gauge, which was significantly lower than the self-adhesive gel prepared in Example 1 ( Figure 3 ).

[0103] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. An injectable self-adhesive gel, characterized in that It comprises an oil phase dispersant and polyelectrolyte complex particles uniformly dispersed in the oil phase dispersant; The polyelectrolyte complex particles are obtained by coagulating, drying and ball milling a cationic polyelectrolyte and an anionic polyelectrolyte modified with phenylboronic acid in a solution.

2. The injectable self-adhesive gel according to claim 1, characterized in that The cationic polyelectrolyte modified with phenylboronic acid is obtained by covalently grafting a molecule with phenylboronic acid groups with a cationic polyelectrolyte; The molecule with phenylboronic acid group includes at least one of 3-acrylamidophenylboronic acid, 4-carboxyphenylboronic acid and 3,4-dicarboxyphenylboronic acid; The covalent grafting comprises at least one of a Michael addition reaction and an amidation reaction; In the modified phenylboronic acid cationic polyelectrolyte, the grafting rate of phenylboronic acid groups is 1% to 20%, preferably 2% to 10%; the grafting rate of phenylboronic acid groups refers to the molar ratio of phenylboronic acid groups to repeating units in the cationic polyelectrolyte.

3. The injectable self-adhesive gel according to claim 1 or 2, characterized in that The cationic polyelectrolyte in the cationic polyelectrolyte modified with phenylboronic acid comprises at least one of polyethyleneimine, polylysine, poly(lysine-leucine), and chitosan; The anionic polyelectrolyte includes at least one of polyacrylic acid, hyaluronic acid and heparin.

4. The injectable self-adhesive gel according to claim 1, characterized in that The mass ratio of the oil phase dispersant to the polyelectrolyte complex particles is 4 to 12:1, preferably 6 to 9:

1.

5. The injectable self-adhesive gel according to claim 1, characterized in that The weight average molecular weights of the cationic polyelectrolyte and the anionic polyelectrolyte in the cationic polyelectrolyte modified with phenylboronic acid are independently 10,000 to 400,000 g / mol, preferably 10,000 to 200,000 g / mol; The polyelectrolyte complex particles are obtained by coagulating, drying and ball milling a cationic polyelectrolyte and an anionic polyelectrolyte modified with phenylboronic acid in a molar ratio of 0.1 to 5:1 in a solution.

6. The injectable self-adhesive gel according to claim 1, characterized in that The particle size of the polyelectrolyte complex particles is 1 to 100 microns, preferably 5 to 10 microns.

7. The injectable self-adhesive gel according to claim 1, characterized in that The oil phase dispersant includes at least one of glycerol and linoleic acid.

8. The injectable self-adhesive gel according to claim 1 or 7, characterized in that The oil phase dispersant includes glycerol and linoleic acid; In the oil phase dispersant, the volume ratio of glycerol to linoleic acid is 0.2-5:

1.

9. The method for preparing an injectable self-adhesive gel according to any one of claims 1 to 8, characterized in that: include: Phenylboronic acid groups are introduced by covalently grafting molecules with phenylboronic acid groups with cationic polyelectrolytes to obtain cationic polyelectrolytes modified with phenylboronic acid; The cationic polyelectrolyte and the anionic polyelectrolyte modified with phenylboronic acid are coagulated, dried and ball-milled in a solution to obtain polyelectrolyte complex particles; The polyelectrolyte complex particles are uniformly dispersed in an oil phase dispersant to obtain the injectable self-adhesive gel.

10. Use of the injectable self-adhesive gel according to any one of claims 1 to 8 in the preparation of vascular embolic materials.